Estimating the consequences of multiple threats and management strategies for semi‐aquatic turtles. Issue 2 (10th January 2014) - Crawford, Brian A.; Maerz, John C.; Nibbelink, Nathan P.; Buhlmann, Kurt A.; Norton, Terry M.; Dickman, Christopher
Summary Roads are pervasive fixtures on most landscapes but are typically among many factors contributing to wildlife population declines. Addressing road mortality as part of larger conservation efforts is challenging because it can be difficult to measure per capita mortality from roads and other concurrent threats. We used 4 years of mark–recapture–recovery data for diamondback terrapins Malaclemys terrapin on a causeway in Georgia, USA, to directly estimate threats of adult road mortality and nest predation, contrast the consequences to population growth using stage‐based matrix models and make management recommendations to stabilize the population. Mean estimated annual adult road mortality was 11·1% (range = 4·4–16·4%). Estimated annual nest predation was 61·9%. We estimated that the population was declining (λ < 0·98) in all scenarios where both threats were included. Variation in adult survival was the most influential (highest elasticity) contributor to population growth relative to other demographic rates; however, λ would remain below 1 with any nest predation rate exceeding our estimate even if actions to mitigate road mortality were 100% effective. Synthesis and applications. Our study provides some of the first direct estimates of vehicle mortality rates and shows that mortality can remain sufficiently high among years to cause population declines. We also demonstrate that management actions focused on singular threats are inadequate for recovering populations. We conclude that integrated road and predator management is necessary to conserve turtle populations, and we suggest alternative strategies to compensate for some vehicle mortality and nest depredation.